The Influence of Work Motivation on the Professionalism of Science Teachers in Elementary School Kutai Village - Rediyono Rediyono (Jurnal Penelitian Pendidikan IPA, 2026)
The study was conducted in an elementary school in Kutai Village. The population of the study was The population in this study were all elementary school science teachers in Kutai Village, totaling 111 teachers spread across 28 schools. Of the 111 teachers in the population, 53 were selected as samples using a random sampling technique with the Taro Yaname and Slovin formula with a precision of 10%. The data collection technique in this study used a questionnaire with a Likert scale. In addition, documentation techniques were used to obtain supporting data related to school conditions and teacher profiles. The research instrument used was a closed questionnaire that was first tested for validity and reliability. Validity testing was carried out to determine the extent to which the instrument was able to measure what should be measured, while reliability testing was carried out to determine the level of consistency of the research instrument. The collected data were analyzed using statistical analysis techniques. The results of the study indicate that the work motivation of elementary school teachers in Kutai Village has a low and insignificant relationship with their professional abilities (0.309). The contribution of teacher work motivation in rural areas is also insignificant, at 9.5%. In addition, teachers also experience obstacles in developing their professionalism. This study recommends that local governments provide stimulus and encouragement to teachers in rural areas to continue developing their professionalism. The implication is the need for a more comprehensive approach in efforts to improve the professionalism of science teachers in elementary schools in Kutai Village. Increasing teacher work motivation alone is not enough to produce optimal professionalism if it is not accompanied by structural and institutional support